Average Error: 0.0 → 0.0
Time: 13.5s
Precision: 64
${2}^{\left(-x\right)} + {x}^{\left(-2\right)}$
${2}^{\left(-x\right)} + {x}^{\left(-2\right)}$
{2}^{\left(-x\right)} + {x}^{\left(-2\right)}
{2}^{\left(-x\right)} + {x}^{\left(-2\right)}
double f(double x) {
double r32734855 = 2.0;
double r32734856 = x;
double r32734857 = -r32734856;
double r32734858 = pow(r32734855, r32734857);
double r32734859 = -r32734855;
double r32734860 = pow(r32734856, r32734859);
double r32734861 = r32734858 + r32734860;
return r32734861;
}


double f(double x) {
double r32734862 = 2.0;
double r32734863 = x;
double r32734864 = -r32734863;
double r32734865 = pow(r32734862, r32734864);
double r32734866 = -r32734862;
double r32734867 = pow(r32734863, r32734866);
double r32734868 = r32734865 + r32734867;
return r32734868;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

${2}^{\left(-x\right)} + {x}^{\left(-2\right)}$
2. Final simplification0.0

$\leadsto {2}^{\left(-x\right)} + {x}^{\left(-2\right)}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "pow(2,-x)+pow(x,-2)"
(+ (pow 2.0 (- x)) (pow x (- 2.0))))